1987
DOI: 10.1200/jco.1987.5.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine clearance as a predictor of ultrafilterable platinum disposition in cancer patients treated with cisplatin: relationship between peak ultrafilterable platinum plasma levels and nephrotoxicity.

Abstract: Ultrafilterable platinum (UP) disposition was studied in 22 cancer patients receiving their first course of cisplatin (50 to 140 mg/m2) by two-hour infusion. UP plasma and urinary platinum levels were quantitated using a high-performance liquid chromatographic (HPLC) assay, which was selective for cisplatin and active platinum metabolites. Creatinine clearance was determined in all patients at the time of the pharmacokinetic studies and ranged from 58 to 214 mL/min. Creatinine clearance was a poor predictor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 4 publications
5
49
0
1
Order By: Relevance
“…This has also been described for patients receiving conventional cisplatin treatment (Stewart et al, 1997). Various studies have demonstrated that cisplatin-induced nephrotoxicity is related to the peak plasma concentration and/or the area under the plasma concentration -time curve of nonprotein bound cisplatin (Reece et al, 1987;Nagai et al, 1996;Nagai and Ogata, 1997). It is postulated that low serum albumin concentrations are associated with increased plasma concentrations of unbound cisplatin, resulting in enhanced renal toxicity.…”
Section: Discussionmentioning
confidence: 90%
“…This has also been described for patients receiving conventional cisplatin treatment (Stewart et al, 1997). Various studies have demonstrated that cisplatin-induced nephrotoxicity is related to the peak plasma concentration and/or the area under the plasma concentration -time curve of nonprotein bound cisplatin (Reece et al, 1987;Nagai et al, 1996;Nagai and Ogata, 1997). It is postulated that low serum albumin concentrations are associated with increased plasma concentrations of unbound cisplatin, resulting in enhanced renal toxicity.…”
Section: Discussionmentioning
confidence: 90%
“…Considerable interindividual differences in toxicity were apparent in this study, even between patients of similar age and receiving similar administration schedules and total doses of cisplatin. It is possible that interindividual variability in cisplatin pharmacokinetics may be at least partly responsible (Reece et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In recent series the mean fall in glomerular filtration rate during cisplatin therapy has been reported as low as 0% (Swainson et al, 1985) and as high as 29% (Reece et al, 1987), although with different schedules of treatment. Previous studies have related the extent of cisplatin nephrotoxicity to peak levels of ultrafiltrable platinum and thus to duration of administration and dose received (Reece et al, 1987). The question of cumulative toxicity is more controversial.…”
Section: Renal Functionmentioning
confidence: 99%